Optimization of pH Conditions for Lead Adsorption using Ion-Imprinted Polymer (IIP) with EDTA as Ligand - Permatasari, Yuliani; Sianita, Maria Monica (Universitas Islam Indonesia, 2025)
Ion-imprinted polymers (IIPs) are selective adsorbents for heavy metal removal. In this study, IIPs were synthesized using Pb²⁺ as a template, EDTA as a ligand, methacrylic acid (MAA) as a monomer, and ethylene glycol dimethacrylate (EGDMA) as a crosslinker via precipitation polymerization in an ethanol-acetonitrile mixture with benzoyl peroxide (BPO) as an initiator at 70°C. FTIR analysis confirmed the successful synthesis of IIPs by identifying Pb-O vibrations at 530.1 cm⁻¹ in the non-imprinted polymer (NIP), which disappeared in IIP after Pb²⁺ removal. SEM-EDX analysis showed IIP had more voids than NIP due to Pb²⁺ removal, with decreased Pb content from 1.85% to 0.18%. Adsorption was tested at pH 4–9, a 30-minute contact time, and an initial Pb²⁺ concentration of 50 ppm. The optimum pH was 7, with an adsorption capacity of 47.52 mg/g and a percentage recovery of 97.3%. This method offers higher selectivity, stability, and reusability due to the polymer matrix's specific Pb²⁺-imprinted cavities than other adsorption methods. Adsorption occurred via electrostatic interactions and complex formation. These results demonstrate that IIPs are effective for Pb²⁺ removal, offering a promising solution for heavy metal pollution treatment.